2011
DOI: 10.1016/j.ajpath.2010.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Expressing Cyclooxygenase-2 in Hepatocytes Reveal a Minor Contribution of This Enzyme to Chemical Hepatocarcinogenesis

Abstract: Cyclooxygenase-2 (COX-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Moreover, recent data and our present results indicate that COX-2 mRNA levels are significantly higher in the adjacent liver than in the HCC and lower in HCC than in nonalcoholic steatohepatitis [12]. Our previous work demonstrated that COX-2 expression is not sufficient to enhance malignant transformation induced by dyethylnitrosamine in a model of transgenic mice expressing COX-2 in hepatocytes [33]. These results suggest that COX-2 could be related to the inflammatory response occurring in the early phases of chronic liver disease and eventually contribute to the induction of hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Moreover, recent data and our present results indicate that COX-2 mRNA levels are significantly higher in the adjacent liver than in the HCC and lower in HCC than in nonalcoholic steatohepatitis [12]. Our previous work demonstrated that COX-2 expression is not sufficient to enhance malignant transformation induced by dyethylnitrosamine in a model of transgenic mice expressing COX-2 in hepatocytes [33]. These results suggest that COX-2 could be related to the inflammatory response occurring in the early phases of chronic liver disease and eventually contribute to the induction of hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 46%
“…pPyCAGIP-hCOX-2 was prepared as described previously [33]. Briefly, human COX-2 ORF was amplified by PCR from human full-length COX-2 cDNA cloned into pcDNA1/Amp, and then, was subcloned into Xho I- Not I restriction site of pPyCAGIP vector.…”
Section: Methodsmentioning
confidence: 99%
“…However, although COX-2 expression is detected in early phases of HCC, contradictory observations have been published regarding the nature of the cells expressing the enzyme (both in normal hepatocytes and in hepatoma cells), the role of this expression pattern and the molecular mechanisms by which COX-2-dependent PGs contribute and/or induce tumorigenesis. Interestingly, work from our group[ 51 ] has shown that COX-2 expression is not sufficient to exacerbate malignant transformation after administration of chemical hepatocarcinogens. Even more, progression of liver oncogenesis in a well-established model of HCC (the c-myc and TGF-α double transgenic mice), is not affected by COX-2 expression[ 52 ].…”
Section: Cox-2 and Hccmentioning
confidence: 99%
“…The PTPRJ ( DEP1 ) cDNA construct was a kind gift from Dr. Nicholas K Tonks (Cold Spring Harbor Laboratory, NY, USA) [27] . The plasmids encoding COX-2 was a kind gift from Dr. Marta Casado (Institute of Biomedicine of Valencia, Valencia, Spain) [28] .…”
Section: Methodsmentioning
confidence: 99%